Revisiting Baumol's Disease: Structural Change, Productivity Slowdown and Income Inequality - Jochen Hartwig; Hagen M. Krämer (Intereconomics, 2023)
The growing importance of services has led to significant structural change in advancedeconomies, with the service sector now accounting for the largest share of employment indeveloped countries. In his seminal model of the so-called cost disease of services, WilliamBaumol noted that the prices of services, especially in health, education, arts and culture,tend to rise faster than the prices of material goods. Central to his model is the disparityin labour productivity growth rates between stagnant and progressive sectors. Baumol'smodel sheds light on the reasons behind the rising cost of services and provides a deeperunderstanding of its economic consequences. This article argues that Baumol's model ofthe cost disease of services retains its explanatory power and relevance today. It refutescriticisms that productivity growth in services is mismeasured and underestimated and thatthe increasing importance of services as inputs in manufacturing renders Baumol's modelirrelevant. Instead, the article argues that Baumol's model can highlight the overlookedconsequences of rising income inequality, particularly the severe impact of the cost disease,which disproportionately affects the poorer segments of the population.
Keywords: B20; L16; L84; I14; 330; income distribution; productivity; productivity development; structural change; Einkommensverteilung; Produktivität; Produktivitätsentwicklung; Strukturwandel; Welt